Disclosure of information on hygiene and changing habits during the Covid-19 pandemic (Research, Society and Development, 2021)
Covid-19 is an acute respiratory disease, caused by the SARS-CoV-2 virus, which was categorized as a pandemic in 2020. Its contamination occurs through droplets of the active virus, which can be transmitted between individuals or through contaminated objects. Based on these aspects, the present study aimed to verify whether the search for information on hygiene measures promoted changes in habits in hygiene practices during the Covid-19 pandemic. For this, a cross-sectional study was carried out through an online questionnaire (on the Google forms platform), which contained questions related to the health emergency period. Data analysis was performed using descriptive and inferential statistics using Pearson's chi-square test. Among the respondents, the majority declared to seek information on hygiene to mitigate the contamination of the coronavirus during the pandemic period, with emphasis on specific information on food hygiene. The most used strategies to obtain information on hygiene practices were: internet, news, and e-book on good Coronavirus prevention practices. Among these, the internet had a positive influence on food hygiene habits and the correct use of a mask. It was also observed that the participants changed the habits of purchasing food with regard to observing the expiration date and cleaning the packaging at home. It is possible to conclude that the pandemic period generated important changes in the hygiene habits of the population studied, and that health education strategies can generate positive changes in the practices of producing safe food.